Pengembangan Media Monopoli Cerdas (MONCER) Bertema Budaya untuk Meningkatkan Hasil Belajar - Sri Haryati Rahayuningsih; Yazid Firdiawan; Heri Maria Zulfiati; Daimul Hasanah; Moh Rusnoto Susanto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The learning process that still revolves around teachers using only lecture methods and the lack of utilization of engaging learning media makes learning monotonous and boring. This study aims to develop the Monopoli Cerdas (MONCER) learning media to support the learning process on Theme 8. Bumiku Subtheme 1. Perbedaan Waktu dan Pengaruhnya. This research is a Research and Development (R&D) with the ADDIE development model through the stages of analysis, design, development, implementation, evaluation. The results of the study show that the Monopoli Cerdas (MONCER) media overall obtained a rating with a very feasible category, with the details of the media feasibility percentage as follows: subject matter experts with an average acquisition of 88.02%, media experts with an average acquisition of 83.75%, language experts with an average acquisition of 84.86%. In addition, there was a significant increase in student learning outcomes, namely by 21.13 points, and positive responses from students with a response rate of 91.94%. The MONCER media has been proven suitable for application and effective in increasing students' interest and motivation to learn.